PENGARUH NILAI CADANGAN PANAS BUMI TERHADAP KELAYAKAN PROYEK PENGEBORAN SUMUR EKSPLORASI OLEH PEMERINTAH BERDASARKAN PERBANDINGAN BIAYA DAN PENDAPATAN NEGARA: STUDI KASUS PROYEK NAGE, KABUPATEN NGADA, PROVINSI NUSA TENGGARA TIMUR: GEOTHERMAL RESOURCES EFFECTS ON PROJECT FEASIBILITY OF EXPLORATION WELL DRILLING BY THE GOVERNMENT BASED ON STATE COST AND REVENUE COMPARISON: A STUDY CASE OF NAGE PROJECT, NGADA REGENCY, EAST NUSA TENGGARA PROVINCE - Evi Octavia; Iman K Sinulingga; Fitri Purnamasari Liveta; Husin Setia Nugraha (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2023)
The three main problems in Indonesia's geothermal development include selling price issues, working area tenders, and high upstream risks. These three will lead to one condition: geothermal projects cannot reach their economic level. The Government of Indonesia (GoI) has initiated the Government Drilling Program to reduce high upstream risks. In addition to the main objective of reducing geothermal upstream risk, this program can indirectly generate state revenue. It is necessary to evaluate the program not only from a technical perspective but also from a financial point of view. Stakeholders could consider the evaluation results when making decisions about the continuity of this program. This financial evaluation will assess whether the costs incurred as an investment generate the desired rate of return. In this case, it compares the costs incurred by the GoI from the state budget (APBN) and the revenues obtained by the GoI from tax and non-tax. The Indonesiaost ratio (BCR) value is a parameter indicator of its assessment. The study results show that the BCR value of the government's cash flow from the Nage Project is 2.1. This value indicates that every rupiah of costs incurred by the government in the project will generate more than twice as much state revenue. Using the rate of return parameter, namely the Internal rate of Return (IRR), this project produces a value almost double the rate of return determined if the project uses the state budget. In addition, the Nage Project's valuation based on the Net Present Value (NPV) shows a positive value (NPV> 0). Based on those three indicators, the Government Drilling Program, especially the Nage Project, is feasible to continue. However, when viewed from the developer's cash flow perspective, the Nage Project of 30 MWe is still not attractive to private developers in Indonesia because the value of the project feasibility indicator is negative or –the rate of return is still below the desired value (IRR < MARR - Minimum Attractive Rate of Return ). The project is still feasible to be continued by developers from state-owned enterprises (SOE), which usually have lower MARR values. In addition, SOE has privileges in loan and depreciation parameters compared to private developers.